The Impact of Internet and Videogaming Addiction on Adolescent Vision: A Review of the Literature - Mylona, Ioanna; Deres, Emmanouil S.; Dere, Georgianna-Despoina S.; Tsinopoulos, Ioannis; Glynatsis, Mikes (Frontiers in Public Health, 2020)
During the past decade, vision problems that were attributed to the use of electronic screens have gradually shifted from being a workplace health issue to a wider public health issue. “Computer vision syndrome” originally related to the few professionals exposed to long hours of work in front of a computer screen. The widespread use of digital screens in devices used throughout the day have led to the emergence of “digital eye strain” as a new clinical syndrome that affects every individual who spends a large period of time fixated on multiple screens, for work or leisure. A new subcategory, “video game vision” has been proposed to specifically address vision issues related to large periods of continuous use of screen enabled devices in order to play video games. With gaming disorder being included in the next version of the WHO classification of diseases (ICD-11), it is becoming increasingly important to have a clear idea of the impact of this disorder in general health and functioning. At the same time, a number of research studies have reported positive impact of videogame playing on the players vision. This article reviews the latest research studies on the impact of digital screen enabled devices on adolescent vision in light of the increasing reports of internet addiction and gaming disorder while referencing positive findings of videogaming on vision in order to provide a balanced approach and assist with classification, diagnosis and treatment, while providing directions for future research.